Square Ringforts? A Contribution to the Identification of 'Ringfort' Types. Issue 1 (2nd January 2019) - COMBER, MICHELLE
Abstract : ONGOING DISCUSSIONS of the monuments commonly referred to as 'ringforts' in Ireland include the definition and investigation of specific types of these enclosures. Rectilinear, or subsquare, enclosures comprise one such type, with examples identifiable in the well-preserved archaeological landscape of the Burren (Co Clare) in western Ireland. It is also possible to extend such identification into the counties of the western seaboard, from Co Cork in the south to Co Donegal in the north. Questions of chronology, function, status, and cultural identity are addressed. Although a measure of variation may exist within the category of rectilinear enclosures, there is some uniformity of morphology and chronology and, perhaps, function.